The Emerging Artificial Intelligence and the Green Victimology in Indonesia - Anditya, Ariesta Wibisono; Ran, Duan Yan (Universitas Sultan Ageng Tirtayasa, 2024)
The advancement of artificial intelligence has undeniably fostered progress and expedited human development. Artificial intelligence's capacity to emulate human thinking enables computers to exhibit human-like responsiveness through cognitive processes. Conversely, the advancement of artificial intelligence consumes significant energy and produces heat. A more substantial number of computers is necessary to achieve artificial intelligence that is on par with human thinking. A considerable quantity of computers produce thermal energy, resulting in an adverse impact on the surrounding environment. Under these circumstances, the concept of green victimology should be created. A literature review explored the convergence of AI technology with green victimology. The data selection is derived from secondary sources, such as articles, books, papers, and other written references, including legislation. The data collected will be analysed qualitatively, meaning that only data sources that are relevant and consistent with the situation will be used. The research concludes that the extensive utilisation of computers in advancing AI technology if left unregulated, will result in environmental harm through the emission of excessive heat and the generation of computer trash. Indonesia is fully prepared to implement green policies, supported by appropriate regulations, to demonstrate the importance of protecting the environment. This is based on the understanding that the environment can suffer due to human actions, as shown by the concept of green victimology. Perkembangan artificial intelligence memang membawa kemajuan dan percepatan tumbuh manusia. Kemampuan artificial intelligence untuk berpikir layaknya manusia membuat komputer menjadi responsif bagaikan manusia menggunakan akalnya. Di sisi lain, pengembangan artificial intelligence menyerap banyak energi dan menghasilkan panas. Untuk membuat artificial intelligence berkembang menyamai cara pikir manusia membutuhkan lebih banyak lagi komputer. Banyaknya komputer ini menghasilkan panas dan membuat lingkungan sekitarnya menjadi terkorban. Maka, keadaan demikianlah green victimology harus diperkenalkan. Untuk mencari jawaban atas bersinggungnya teknologi AI dengan green victimology, kajian pustaka dilakukan. Pemilihan data berasal dari data sekunder yaitu seperti artikel, buku, laporan, dan referensi tertulis lainnya termasuk perundang-undangan. Hasil akhir dari pengumpulan data akan dianalisis secara kualitatif, yaitu hanya sumber data yang isinya berkorespondensi dan koheren dengan permasalahan akan diambil. Kesimpulan dari penelitian ini yaitu, penggunaan komputer yang masif untuk pengembangan teknologi AI jika tidak dipantau akan merusak lingkungan dengan pencemaran berupa panas yang berlebihan dan munculnya limbah dari komputer. Walau demikian, Indonesia dengan segala peraturan yang mendukung telah siap untuk menegakkan green policy untuk menunjukkan bahwa lingkungan perlu dilindungi karena dalam pandangan green victimology, lingkungan dapat menjadi korban.